1979
DOI: 10.1073/pnas.76.12.6042
|View full text |Cite
|
Sign up to set email alerts
|

Structure of carboxymyoglobin in crystals and in solution.

Abstract: The configuration of the heme-carbonyl group upon binding of carbon monoxide to sperm whale myoglobin (Mb) in crystals is evaluated on the basis of infrared spectroscopic methods. Multiplets of the totally symmetric C-O stretching mode are observed for the heme-bound ligand near 1933, 1944, and 1967 cm-', corresponding to three different heme-carbonyl conformers. Variations in the relative proportions of these conformers can be induced by incorporation of small fractions of metMb or deoxyMb into MbCO crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 23 publications
6
101
1
Order By: Relevance
“…The CO stretching frequency at equilibrium is shown in the top spectrum. Difference spectra are shown at 125 µs, 250 µs, 375 µs, 500 µs, 1 ms, and 4 ms. quency of 507 cm -1 and corresponding CO stretching frequency of 1945 cm -1 are consistent with a histidine-ligated species (8,15,(29)(30)(31). Since the proximal histidine H93 is absent, there are two strong candidates for histidine ligation: H64 on the distal side and H97 on the proximal side.…”
Section: Discussionsupporting
confidence: 56%
“…The CO stretching frequency at equilibrium is shown in the top spectrum. Difference spectra are shown at 125 µs, 250 µs, 375 µs, 500 µs, 1 ms, and 4 ms. quency of 507 cm -1 and corresponding CO stretching frequency of 1945 cm -1 are consistent with a histidine-ligated species (8,15,(29)(30)(31). Since the proximal histidine H93 is absent, there are two strong candidates for histidine ligation: H64 on the distal side and H97 on the proximal side.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, the spectrum of wtMbCO shows at least three distinct absorption lines, centered at 1934 (A 3 ), 1945 (A 1 ), and 1965 cm -1 (A 0 ). 5,26,27 The A 0 peak, the smallest of the three features at room temperature and neutral pH, is believed to arise from configurations in which the ligand interacts most weakly with H64 because the distal histidine is swung out of the pocket. [36][37][38][39]56 As has been discussed in detail previously 5,8,[57][58][59] Figure 1 suggests that the substitution of the distal histidine (H64) by a valine spectroscopically mimics the A 0 state of wtMbCO.…”
Section: Resultsmentioning
confidence: 99%
“…9 The strong IR absorption of the CO bond [70][71][72] performed iron K-edge polarized XANES investigations of MbCO at 20 and 100 K respectively. Their results largely agree with other previous studies (see Table 1) and only a slight increase in the Fe-C and C-O distances were reported.…”
Section: Mbcomentioning
confidence: 99%